2006
DOI: 10.1016/j.joca.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intra-articular hyaluronic acid in patients with osteoarthritis of the ankle: a prospective study

Abstract: Five weekly intra-articular injections of Artz provide pain relief and functional improvements in patients with Kellgren-Lawrence grades I and II ankle OA. The clinical effect was rapid at 1 week and may last for 6 months or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 17 publications
2
53
0
3
Order By: Relevance
“…Clinical benefit was evaluated by means of different scales (Visual Analogic Scale, Ankle Osteoarthritis Scale, American Orthopaedic Foot and Ankle Society, Short Form -12, Short Form -36, Western Ontario and McMaster Universities Osteoarthritis Index), and the follow -up period varied from 6 to 18 months. In studies performed without control group (Hanson et al, 1999;Luciani et al, 2008;MeiDan et al, 2010;Sun et al, 2006;Valiveti et al, 2006;Witteveen et al, 2008Witteveen et al, , 2010 (Table 2), an improvement in all the outcome measures was reported, with the effect lasting for 18 months (Luciani et al, 2008). However, it is not clear from reports whether the pain reduction was clinically significant, or could be ascribed only to a placebo effect.…”
Section: Ankle Osteoarthritismentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical benefit was evaluated by means of different scales (Visual Analogic Scale, Ankle Osteoarthritis Scale, American Orthopaedic Foot and Ankle Society, Short Form -12, Short Form -36, Western Ontario and McMaster Universities Osteoarthritis Index), and the follow -up period varied from 6 to 18 months. In studies performed without control group (Hanson et al, 1999;Luciani et al, 2008;MeiDan et al, 2010;Sun et al, 2006;Valiveti et al, 2006;Witteveen et al, 2008Witteveen et al, , 2010 (Table 2), an improvement in all the outcome measures was reported, with the effect lasting for 18 months (Luciani et al, 2008). However, it is not clear from reports whether the pain reduction was clinically significant, or could be ascribed only to a placebo effect.…”
Section: Ankle Osteoarthritismentioning
confidence: 99%
“…Only few studies have been performed in ankle osteoarthritis and, among these, four were randomized / controlled trials (level of evidence 1) (Carpenter & Motley, 2008;Cohen et al, 2008;Karatosun et al, 2008;Salk et al, 2005Salk et al, , 2006, while seven studies (Hanson et al, 1999;Luciani et al, 2008;Mei -Dan et al, 2010;Sun et al, 2006;Valiveti et al, 2006;Witteveen et al, 2008Witteveen et al, , 2010 were case series (level of evidence 4). In all these studies, patients suffering from post -traumatic Kellgreen -Lawrence grade II -IV ankle osteoarthritis were enrolled.…”
Section: Ankle Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of contrast dye to delineate the joint may be helpful in cases of severe osteoarthritis or in patients with completes varus or valgus deformities 6 . Diagnostic injections with viscosupplementation are less well established and remain more controversial 25,26 . The landmark used for tibiotalar injection is the soft tissue depression between the medial malleolus and the medial border of the tibialis anterior ( Figure 12).…”
Section: Diagnostic Testing and Proceduresmentioning
confidence: 99%
“…Although corticosteroid injections remain the golden standard, there are an increased number of research articles examining the role of viscosupplementation with hyaluronate (HA) in ankle arthritis 25,26,36,48 . Currently, in the U.S., HA injections are only FDAapproved for the knee and injections into the ankle, shoulder and hip are considered 'off-label' use 49 .…”
Section: Viscosupplementationmentioning
confidence: 99%